Effect of different levels of hydrocolloids on viscosity and cloud stability of kinnow juice and beverages. Issue 10 (9th August 2020) - Aggarwal, Poonam; Kumar, Vikas; Yaqoob, Mudasir; Kaur, Sukhpreet; Babbar, Neha
Abstract: Five hydrocolloids that is, gum acacia, CMC, pectin, guar gum, and sodium alginate at different levels from 0.02% to 0.5% in juice and RTS and from 0.1% to 1.0% in squash were added to analyze their effect on viscosity and suspension of kinnow juice and beverages. Juice and beverages containing CMC and sodium alginate showed significantly higher cloud stability and suspension than other hydrocolloids. Juice and RTS containing CMC were found to have maximum viscosity followed by sodium alginate, pectin, and gum acacia. Shear stress versus shear rate in kinnow juice and beverages containing different hydrocolloids showed mostly newtonian to pseudo plastic behavior. Squash with added hydrocolloids showed significant increase in the viscosity, maximum being in sodium alginate followed by CMC, pectin, acacia, and control. After 6 months storage juice and beverages containing CMC were found to have more stable cloud and suspension (especially in squash i.e., 100%) than other hydrocolloids. Practical applications: The developed technology will help the industry and researchers for improving the viscosity and suspension of the kinnow juice and beverages effectively.